Evaluación de la significancia del potencial agroforestal y el beneficio para el asociado de la APAVAM - Dávila Reátegui, Hans (2010)
In order to determine the potential of agroforestry associated with the culture of coffee, the agroforestry systems were valued by the characterization of the sample of coffee farmers of the Association of Agricultural Producers of the Valley Alto Mayo "APAVAM" and the dasometry of the tree component which accompanies the coffee crop developed in the high basin of the Rio May of the Peruvian department San Martin between 838 and 1797 m., characterized by a moderate subtropical climate, with average temperatures of 23.2 °C; 82.3 % of relative dampness and 1200 mm of annual rainfall. Results indicate that the producers have an area total of 10,54 ha of which 3,62 ha is coffee in 9.78 years of age with a productivity of 15,97 qq.ha-1 where labour is distributed between 27 % producer, 24 % wife, 20 % children and 29 % rented. 27 ligneous species of which according to its classification by immediate use54% are of wood value and the remaining 46% are of fruit value and firewood were found in agroforestry systems. The vegetation consists of 64,54 % of species of the genus inga sp that represents the maximum value of importance of 0,32 % rate. Alpha diversity (Simpson λ) is 0.47 3.27 sp.ha-1 of 0.19 m in diameter, with an average of 1.09 m2 of basal area species occupancy. The agroforestry system has a potential equivalent to 108,47 tn.ha-1 of biomass forestry, 81,21 C.tn.ha-1 of stock of carbon with a molecular carbon flow equal to 2.53 C.tn.ha-1.year-1.